Starvation Promotes Autophagy-Associated Maturation of the Ovary in the Giant Freshwater Prawn, Macrobrachium rosenbergii - Kankuan, Wilairat; Wanichanon, Chaitip; Titone, Rossella; Engsusophon, Attakorn; Sumpownon, Chanudporn; Suphamungmee, Worawit; Morani, Federica; Masini, Matilde; Novelli, Michela; Isidoro, Ciro; Sobhon, Prasert (Frontiers in Physiology, 2017)
Limitation of food availability (starvation) is known to influence the reproductive ability of animals. Autophagy is a lysosomal driven degradation process that protects the cell under metabolic stress conditions, such as during nutrient shortage. Whether and how starvation-induced autophagy impacts on the maturation and function of reproductive organs in animals are still open questions. In this study, we have investigated the effects of starvation on histological and cellular changes that may be associated with autophagy in the ovary of the giant freshwater prawn, Macrobachium rosenbergii. To this end, the female prawns were daily fed (controls) or unfed (starvation condition) for up to twelve days, and the ovary tissue was analyzed at different time-points. Starvation triggered ovarian maturation, and concomitantly increased the expression of autophagy markers in vitellogenic oocytes.The immunoreactivities for autophagy markers, including Beclin1, LC3-II, and Lamp1, were enhanced in the late oocytes within the mature ovaries, especially at the vitellogenic stages. These markers co-localized with vitellin in the yolk granules within the oocytes, suggesting that autophagy induced by starvation could drive vitellin utilization, thus promoting ovarian maturation.